Analisis Kesulitan Belajar Membaca Al-Qur'an Pada Siswa Kelas VIII SMP Muhammadiyah 1 Surakarta Tahun Pelajaran 2016/2017 - Pratiwi, Dhevi Kartika Nur, Dr. Mohamad Ali, S.Ag, M.Pd (2017)
SMP Muhammadiyah 1 Surakara has a mandatory learning program to read Al-Qur'an which is manifested in the form of extracurricular activities of MMA. All students in VII grade are required to follow this program so they can read the Qur'an fluently. But in reality there are still students of class VIII who can not read the Qur'an, so they still have to follow the extracurricular activities of MMA. The VIII students who can not read the Qur'an because they have difficulty in learning to read the Al-Qur'an, it is also caused by several factors that come from within and outside of students. Based on this background, the purpose of this study is to identify and describe the difficulties felt by students of VIII grade in learning to read the Qur'an, as well as the factors that cause the students of VIII grade difficulty in learning to read the Qur'an. This research is a field research, ie research activities conducted in a particular school environment by going directly to the intended object. The method used in this research are interviewing, observation, and documentation. While the method of data analysis is done by descriptive, ie the disclosure of the state as it is. The results of the study can be concluded that the difficulties felt by students when learning to read Al-Qur'an is difficulty memorizing attributes due to the characteristics and forms in some letters hijaiyah, the difficulty of understanding the change in the form of hijaiyah letters serialized with other hijaiyah, not memorized harakat, difficulty Distinguish long and short haraks, difficulty pronunciation of the right makhraj, and difficulties in applying the law of tajwid. The factors that cause difficulties in learning reciting the Qur'an for students are the internal factor and the external factor. The internal factors are becaue the students are not interested with the learning reciting the Qur'an, they are less-motivated in learning Qur'an, their tongues are not familiar with the reciting Qur'an and spelling the hijaiyah letters. The externaf factors are because the family educatin, the background of the elementary school that does not teach the student how to recite Qur'an, the relationship of the students in their school and neighborhood, the lack of the learning Qur'an lesson in the school, the lack of engagement between student and the teacher. Keywords: difficulty learning, reading al-qur'an, student of class VIII